2015
DOI: 10.1093/mnras/stv523
|View full text |Cite
|
Sign up to set email alerts
|

The luminosity of Population III star clusters

Abstract: We analyze the time evolution of the luminosity of a cluster of Population III protostars formed in the early universe. We argue from the Jeans criterion that primordial gas can collapse to form a cluster of first stars that evolve relatively independently of one another (i.e., with negligible gravitational interaction). We model the collapse of individual protostellar clumps using 2+1D nonaxisymmetric numerical hydrodynamics simulations. Each collapse produces a protostar surrounded by a massive disk (i.e., M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…This is driven by the inward migration of the fragments due to strong gravitational torques caused by the asymmetric disk structure (e.g., spiral arms). As a result, accretion histories normally become highly variable, resulting in short accretion bursts followed by relatively long quiescent phases (e.g., Smith et al 2012;Vorobyov et al 2013;DeSouza & Basu 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This is driven by the inward migration of the fragments due to strong gravitational torques caused by the asymmetric disk structure (e.g., spiral arms). As a result, accretion histories normally become highly variable, resulting in short accretion bursts followed by relatively long quiescent phases (e.g., Smith et al 2012;Vorobyov et al 2013;DeSouza & Basu 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent numerical hydrodynamics simulations of primordial disc formation around the first very massive stars have also revealed the presence of accretion bursts caused by disc gravitational fragmentation followed by rapid migration of the fragments onto the protostar (Stacy et al 2010;Greif et al 2012;Smith et al 2012;Vorobyov et al 2013;Hosokawa et al 2016). These studies have revealed highly variable protostellar accretion with multiple bursts, exceeding in numbers their present-day counterparts (DeSouza & Basu 2015). The same process of bursts driven by disc fragmentation operates around primordial super-massive stars, relaxing the ultraviolet photon output and enabling the stellar growth to the limit where general-relativistic instability results in the formation of super-massive black holes (Sakurai et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The shocks are therefore traced by the non-thermal radio knots and Herbig-Haro (HH) objects. Some of the theories put forward to explain how shocks are formed in YSOs include episodic accretion (DeSouza & Basu 2015) and interaction between jet material with the ambient medium and/or internal working surfaces within the jet (Rubini et al 2007). Star formation models that incorporate disks can explain how the shocks are formed in MYSOs.…”
Section: Introductionmentioning
confidence: 99%